2021
DOI: 10.1016/j.landusepol.2020.105129
|View full text |Cite
|
Sign up to set email alerts
|

Are women neglected in the EU agriculture? Evidence from Lithuanian young farmers

Abstract: Highlights Gender-wise differences in the perceptions of young farmers. The measures of the Common Agricultural Policy. Development of farms and the use of advisory services. The results show gender equality in Lithuanian agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…First, the study focused on understanding an under-researched area, using a sample of Black farmers turned entrepreneurs into an occupational space that has been not only politicised (Nenzhelele et al, 2020) but also historically contested (Nieuwoudt, 2000;Van Averbeke and Mohamed, 2006). By magnifying Black farmers' experiences amid calls for social transformation efforts, this study answers calls for such studies (Nye, 2020;Balezentis et al, 2021). Second, the study through the portrayed lives of Black entrants into agriculture as entrepreneurs sets the tone of empirical evidence illustrating how racial and historical hegemonies are dismantled (Van Sant, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the study focused on understanding an under-researched area, using a sample of Black farmers turned entrepreneurs into an occupational space that has been not only politicised (Nenzhelele et al, 2020) but also historically contested (Nieuwoudt, 2000;Van Averbeke and Mohamed, 2006). By magnifying Black farmers' experiences amid calls for social transformation efforts, this study answers calls for such studies (Nye, 2020;Balezentis et al, 2021). Second, the study through the portrayed lives of Black entrants into agriculture as entrepreneurs sets the tone of empirical evidence illustrating how racial and historical hegemonies are dismantled (Van Sant, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers (Herren et al, 2011) have emphasized societal-communal factors such as parents, teachers and friends' influence in encouraging a focus on the agriculture space as a career path. The thinking could be that agricultural activities are often communal, with skills imparted from one generation to another (Balezentis et al, 2021). Equally important could be an interest in agriculture through observing others and, in turn, learning a trade (Adeagbo and Adejumo, 2020).…”
Section: Motivational Factors Into Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Progress in regional development, strengthening financial resources and using social capital are effective in empowering women in smallholder land systems. Balezentis et al (2021) in his study, looked at the differences between the education levels of men and women and concluded that if women were more literate and knowledgeable in Lithuanian agriculture, they would have a positive impact on agricultural innovation. Women's participation in agriculture and an increase in their environmental awareness expands the inclination to innovation and economic resilience.…”
Section: Bamarinejad Et Al (mentioning
confidence: 99%
“…For example, the integration between agriculture, livestock, and forest in Sertão has shown to present soils that are more resistant and resilient to prolonged droughts, especially the surface soil [ 19 ]. The extensive livestock production prevailing in the Sertão presents the lowest stocking rates in Brazil, and are primarily dependent on local natural resources [ 20 ]. Therefore, the preservation of the natural vegetation might be fundamental to sustain the long-term cattle raising in the region.…”
Section: Introductionmentioning
confidence: 99%